COTTON GROWING AND COTTON SOLOISM IN THE FERGANA REGION AT THE END OF THE XIX - BEGINNING OF THE XX CENTURIES OCCURRENCE (Scientific journal of the Fergana State University, 2026)
The article reflects on the measures taken by colonial authorities to develop cotton farming in the Fergana region after the occupation of St. Petersburg and on the basis of local archival documents and other historical sources. Attempts have also been made to uncover changes in agriculture, the plight of farmers, the foundation and consequences of cotton solitary confinement.